Pricing recreation use of national parks for an efficient nature conservation: an application to the portuguese case - Mendes, Isabel (2003)
Current institutions, research, and legislation have not yet been sufficient to achieve the conservation level of Nature as required by the society. One of the reasons that explains this relative failure is the lack of incentives to motivate local individual and Nature users in general, to adopt behaviour compliant with Nature sustainable uses. Economists believe that, from the welfare point of view, pricing is the more efficient way to make economic actors to take more environmental friendly decisions. In this paper we will discuss how efficient can be the act of pricing the recreation use of a specific natural area, in terms of maximising welfare. The main conservation issues for pricing recreation use, as well as the conditions under which pricing will be an efficient and fair instrument for the natural area will be outlined. We will conclude two things. Firstly that, from the rational utilitarian economic behaviour point of view, economic efficiency can only be achieved if the natural area has positive and known recreation marginal costs under the relevant range of the marshallian demand recreation curve and if price system management is not costly. Secondly, in order to guarantee equity for the different type of visitors when charging the fee, it is necessary to discuss differential price systems. We shall see that even if marginal recreation costs exist but are unknown, pricing recreation is still an equity instrument and a useful one from the conservation perspective, as we shall demonstrate through an empirical application to the Portuguese National Park. An individual Travel Cost Method Approach will be used to estimate the recreation price that will be set equal to the visitor's marginal willingness to pay for a day of visit in the national park. Although not efficient, under certain conditions this can be considered a fair pricing practice, because some of the negative recreation externalities will be internalised. We shall discuss the conditions that guarantee equity on charging for the Portuguese case.